3_D surface stereometry of Ag/DLC nanocomposite prepared by RF-PECVD - Stach, Sebastian; Ţălu, Ştefan; Abdolghaderi, Senour; Shafiekhani, Azizollah; Bahmani, Jahangir (Results in physics, 2019)
•We characterized the structural complexity of the 3-D surface of the Ag/DLC nanocomposite prepared by RF-PECVD.•The 3-D surface analysis of the samples was performed using an atomic force microscope operating in contact mode.•We determined the statistical surface parameters by stereometric analysis. In this study, a stereometric analysis of the three-dimensional (3-D) surfaces of the Ag/diamond-like carbon (DLC) nanocomposite films was done. The nanocomposite thin films were fabricated by Radio Frequency Plasma-Enhanced Chemical Vapour Deposition (RF-PECVD). The 3-D surface microtexture was studied by high-resolution Atomic Force Microscopy (AFM) records combined with statistical analyses. More detailed information about surface statistical parameters and topographic features of analyzed samples were performed. The statistical parameters relating to the segmented motifs consistent with ISO 25178-2: 2012 have been generated using MountainsMap® Premium software. The analysis was performed by modeling Ag/DLC nanocomposite surface microtexture based on motif analysis (detection of essential characteristics in terms of surface dimensions, volume, curvature, shape) to be included in computer interactive simulation algorithms.